Physiological demands of simulated elite Karate kumite matches - le Roux, E.; Coetzee, F. F.; van Rensburg, C. J.; Schall, R. (African Journal for Physical, Health Education, Recreation and Dance, 2016)
The purpose e of this study was to determine the physiological demands during simulated karate kumite matches. Twelve elite male karatekas who regularly participate in national and international events were recruited from the Free State Karate High Performance Squad in Bloemfontein, South Africa. Selected tests were performed, including anthropometry, a graded maximal oxygen uptake effort test (VO2max), and a simulated kumite competition. During the competition, the heart rate (HR), breathing rate (BR) and estimated core temperature were recorded by the Zephyr BioHarnessTM 3 System. All matches were video-recorded and analysed by a video software program (Dartfish). Athletes achieved a higher maximal heart rate (HRmax) during the simulated kumite matches than during the VO2max test (187.5 < 190.8 bpm). There was a 55.4% aerobic and 44.5% anaerobic energy system contribution during the respective kumite matches, with an effort-to-rest ratio of ~1.5:1. A statistically significant difference (P=0.05) was found between rounds regarding the means calculated for the mean HR during the fight (F=7.05; P=0.03). A karate kumite match can be characterised as a high-intensity activity with regard to physiological variables, where athletes are subjected to maximal cardiovascular responses. It is therefore advisable that coaches remain focused on the technical and tactical aspects of training, and that conditioning specialists focus more on improving the athletes' ability to sustain highintensity activities during conditioning sessions